2005
DOI: 10.1016/j.molcel.2005.08.030
|View full text |Cite
|
Sign up to set email alerts
|

Downregulated REST Transcription Factor Is a Switch Enabling Critical Potassium Channel Expression and Cell Proliferation

Abstract: Induction of K(Ca)3.1 (IKCa) potassium channel plays an important role in vascular smooth muscle cell proliferation. Here, we report that the gene encoding K(Ca)3.1 (KCNN4) contains a functional repressor element 1-silencing transcription factor (REST or NRSF) binding site and is repressed by REST. Although not previously associated with vascular smooth muscle cells, REST is present and recruited to the KCNN4 gene in situ. Significantly, expression of REST declines when there is cellular proliferation, showing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
137
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(146 citation statements)
references
References 34 publications
8
137
0
1
Order By: Relevance
“…In these mice, the expression of REST did not alter the architecture of pancreatic islets, but induced a reduction in the number of beta cells. This effect is consistent with the anti-proliferative action of REST, previously reported in tumoral transformation [41] and human neointimal hyperplasia [9]. The reduced number of cells correlated with reduced expression of the insulin gene and lower pancreatic content of the hormone, which was not observed in INS1-E cells acutely transduced for REST.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In these mice, the expression of REST did not alter the architecture of pancreatic islets, but induced a reduction in the number of beta cells. This effect is consistent with the anti-proliferative action of REST, previously reported in tumoral transformation [41] and human neointimal hyperplasia [9]. The reduced number of cells correlated with reduced expression of the insulin gene and lower pancreatic content of the hormone, which was not observed in INS1-E cells acutely transduced for REST.…”
Section: Discussionsupporting
confidence: 90%
“…Previous reports have identified some of these target genes and their function in and outside the nervous system. Thus, it is now documented that REST target genes are involved in the reactivation of the fetal cardiac gene programme in hypertrophied and failing hearts [8], and modulate the vascular plasticity/remodelling of human neointimal hyperplasia [9].…”
Section: Introductionmentioning
confidence: 99%
“…Overexpression of alternatively spliced forms of REST that function as dominant negatives has also been shown to promote tumorigenesis (26,27). Importantly, down-regulation of REST has been shown to enable gene expression that promotes vascular SMC proliferation (43). The role of REST in myometrial SMCs or its loss in the pathogenesis of uterine fibroids has not been reported previously.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas the first directly mediate Ca 2Ï© inflow, the latter regulate membrane potential and thus provide the driving force for Ca 2Ï© entry (13). In particular, the intermediate-conductance K Ca (K Ca 3.1) has been shown to play an important role in promoting mitogenesis in several tissues such as the endothelium (15,16), vascular smooth muscle (17)(18)(19), and T lymphocytes (20) as well as in several cell lines including A7r5 neonatal aortic smooth muscle cells (21), 10T1/2-MRF4 myogenic fibroblasts (22,23), HMEC-1 dermal endothelial cells (15), and some cancer cell lines (24,25).…”
mentioning
confidence: 99%